Ragam Budaya Desa Jati Pasar sebagai Aset Menuju Destinasi Wisata yang Berbasis Budaya - Siswo Martono (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
The development of Jatipasar village as a cultural tourism destination is not only to increase the number of visits but also to pay attention to the economic, environmental, social and technological dimensions. This study aims to photograph the potentials that have the opportunity to make Jatipasar village a cultural tourism destination. This type of research is ethnographic qualitative. Data collection by observation, interviews, documentation, literature study and analyzed descriptively. The results of the analysis of Jatipasar village development with the concept of sustainable tours development. There are 4 dimensions that become the principles of development, namely 1) economic, 2) environmental, 3) social and 4) technology. The development of tourist destinations with the concept of sustainable tours development always pays attention to the negative and positive impacts on society.